The Impact of Islam on Pre-Colonial Diplomatic Relations between the Sokoto Caliphate and Neighbouring States - Oladipupo, Awofisayo Albert; Lateef, Rauf Adeola; Adebimpe, Asamu Rasheed (NIU Journal of Humanities; Vol 10 No 4 (2025): NIU Journal of Humanities, Vol. 10 No. 4, December 2025, 2025)
This research explores the influence of Islam on diplomatic interactions between the Sokoto Caliphate and its neighbouring states during the nineteenth century Jihad. The primary aim is to investigate how Islamic principles, legal frameworks, and scholarly connections influenced foreign relations, alliances, and conflict resolution between Sokoto and other Hausa land such as Zauzau, Kano, Rano, Katsina, Daura and other Hausa States. The study utilizes a qualitative historical approach, drawing upon primary materials including correspondence from the caliphate, chronicles from the emirates, and records from the Sokoto archives, alongside secondary literature from existing academic work. Textual and content analyses were performed to interpret diplomatic communications, religious decrees, and reports from emissaries in order to pinpoint Islamic tenets that guided diplomatic engagements. Results indicate that Islam acted not only as a spiritual foundation but also as a diplomatic tool that validated authority, governed warfare through the jihad concept, and enabled peaceful resolutions. Clerical intermediaries and written exchanges developed a shared diplomatic language, while a common Islamic identity opened paths for forming alliances and negotiating autonomy. Nonetheless, in certain instances, religious principles were set aside in favour of political interests, as demonstrated by Sokoto’s practical interactions with non-Muslim neighbours. The conclusion highlights that Islam equipped the Sokoto Caliphate with both normative legitimacy and institutional mechanisms that transformed pre-colonial interstate dynamics in the central Sudan. The paper suggests that modern African nations reconsider the ethical aspects of Islamic diplomatic traditions such as justice, accountability, and peaceful conflict resolution to enhance contemporary methods of resolving disputes, fostering regional cooperation, and engaging in interfaith dialogue. Keywords: Conflict Resolution, Interstate Relations, Islamic Diplomacy, Sokoto Caliphate, Pre-Colonial West Africa.